LUMPUR PANAS LAPINDO: LAHIRNYA SUBYEK DAN PERUBAHAN SOSIAL - Arifin, Muchamad Zaenal; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2016)
ABSTRACT The purpose of this study to describe the social change at lapindo hot mud victims in Porong, Sidoarjo. Themethod of thisresearch is descriptive qualitative to understand how lapindo hot mud victims make a social change as social subject. To collect the data this research use interview, observation, and documents. The results of this study found that many of lapindo hot mud victims started their life from beginning with built a new social construction as a separated subject from their old social form. Through the reform as a subject, lapindo hot mud victims were capable to build social change within social, economic, and cultural aspects. Keyword :Lapindo Hot Mud, Subject, Social Change